Chapter 'A Port of Two Seas.' Lisbon and European Maritime Networks in the Fifteenth Century - Sequeira, Joana (Atti delle «Settimane di Studi» e altri Convegni, 2019)
With the development of research in economic history, historians are now testing the hypothesis that maritime networks and port cities contributed to the phenomenon of European integration. This essay applies a holistic approach to discuss how the city of Lisbon, located outside the privileged setting of multi-cultural interactions that was the Mediterranean Sea, became appealing to merchants from far and wide in late-medieval Europe. To do so, it examines a whole array of commercial, normative, fiscal, royal and judicial sources from European archives to discuss if it is possible to observe this phenomenon of European integration in fifteenth-century Lisbon.